The Supply of Quality in Child Care Centers - Blau, David M.; Mocan, H. Naci (The Review of Economics and Statistics, 2002)
We use data from a sample of child care centers to estimate the relationships between cost and child care quality, and between revenue and quality. We use a measure of child care quality, designed by developmental psychologists, that is positively associated with child development. Taking the estimated cost-quality and revenue-quality relationships as given, we estimate the objective functions of firms and compute the quality supply function. The results indicate that the supply of quality is moderately elastic with respect to price and the wages of child care center workers. Implications of the results for child care policy are discussed.